Hydrological Drivers of Bedload Transport in an Alpine Watershed. Issue 3 (17th March 2022) - Antoniazza, G.; Nicollier, T.; Boss, S.; Mettra, F.; Badoux, A.; Schaefli, B.; Rickenmann, D.; Lane, S. N.
Abstract: Understanding and predicting bedload transport is an important element of watershed management. Yet, predictions of bedload remain uncertain by up to several order(s) of magnitude. In this contribution, we use a 5‐year continuous time series of streamflow and bedload transport monitoring in a 13.4‐km 2 snow‐dominated Alpine watershed in the Western Swiss Alps to investigate hydrological drivers of bedload transport. Following a calibration of the bedload sensors, and a quantification of the hydraulic forcing of streamflow upon bedload, a hydrological analysis is performed to identify daily flow hydrographs influenced by different hydrological drivers: rainfall, snowmelt, and combined rain and snowmelt events. We then quantify their respective contribution to bedload transport. Results emphasize the importance of combined rain and snowmelt events, for both annual bedload volumes (77% on average) and peaks in bedload transport rate. A non‐negligible, but smaller, amount of bedload transport may occur during late summer and autumn storms, once the snowmelt contribution and baseflow have significantly decreased (9% of the annual volume on average). Although rainfall‐driven changes in flow hydrographs are responsible for a large majority of the annual bedload volumes (86% on average), the identified melt‐only events also represent a substantial contribution (14% on average). The results of this study help to improve current predictions of bedload transport through a better understanding of the bedload magnitude‐frequency relationship under different hydrological conditions. We further discuss how bedload transport could evolve under a changing climate through its effects on Alpine watershed hydrology. Plain Language Summary: Understanding and predicting bedload transport is an important element of watershed management. Yet, it remains a challenge to predict bedload transport accurately. In this study, we profit from a rare 5‐year continuous time series of streamflow and bedload transport in a 13.4‐km 2 snow‐dominated Alpine watershed in the Western Swiss Alps to investigate the hydrological drivers of bedload transport. An analysis of the streamflow time series together with meteorological data allows classification of daily flow hydrographs over the 5 years of observation between rainfall‐driven, melt‐driven, and a combination of both, and quantification of their contribution with regards to bedload transport. Results of the study show that combined rainfall and snowmelt events with high baseflow are the dominant driver of bedload transport (77% of annual bedload on average), followed to a lower extent by rainfall occurring in the late summer and autumn (9% of annual bedload on average), when the melt contribution and baseflow are lower. The results of this study help to improve current predictions of bedload transport through a better understanding of the bedload magnitude‐frequency relationship under different hydrological conditions. We further discuss how bedload transport could evolve under a changing climate through its effects on Alpine watershed hydrology. Key Points: The co‐occurrence of rainfall in a watershed where the snowmelt signal is strong was the largely dominant driver of bedload transport Melt‐only events, and rainfall events occurring once the melt signal has become smaller, were drivers of secondary importance Combined rain and snowmelt, and melt‐only drivers of bedload transport, may decrease due to climate change impacts on Alpine hydrology